Updates on the use of ureteral stents: focus on the Resonance® stent - Thomas MT Turk (Dove Medical Press, 2010)
Manoj V Rao, Anthony J Polcari, Thomas MT TurkDepartment of Urology, Loyola University Medical Center, Maywood, IL, USAAbstract: The Resonance® metallic ureteral stent is one of the latest additions to the urologist’s armamentarium in managing ureteral obstruction. One advantage of this stent over traditional polymer-based stents is resistance to encrustation with stone material, which allows longer dwell times and less frequent exchange procedures. Although exchanging a metallic stent is slightly more complicated than exchanging a polymer stent, the fluoroscopic techniques required are familiar to most urologists. The Resonance stent is also more resistant to compression by external forces, potentially allowing greater applicability in patients with metastatic cancer. Furthermore, the use of this stent in patients with benign ureteral obstruction is shown to be associated with significant cost reduction. Clinical studies on the use of this stent are accumulating and the results are mixed, although Level 1 evidence is lacking. In this article we present a comprehensive review of the available literature on the Resonance metallic ureteral stent.Keywords: resonance, metallic, ureteral, stent, obstruction